Parenting Patterns for Pre-School Age Children at Al-Khairat Kindergarten - Wahyu; Agustinus Talindong; Jumain; Lexy Kareba; Saiful Ambodale; Parmi (Media Publikasi Promosi Kesehatan Indonesia (MPPKI), 2024)
Introduction: Parenting patterns are classified into three, namely authoritarian parenting models, permissive parenting models and democratic parenting models. During interviews with several children's parents, parents said that their children were difficult to direct, they did not hear what was being said, their children often threw tantrums such as throwing, hitting them if their wishes were not met, there were also children who did not want to talk when gathered with the family, children only wanted to talk. when parents ask. Objective: The aim of the research is to determine the parenting patterns of parents and the emotional development of preschool age children at Al-Khairaat Parigi Kindergarten, Loji Village, Parigi Moutong Regency.. Method: This research method uses a quantitative design with a descriptive research design. The variables in this research are parenting patterns, with the types of data used namely primary data and secondary data, data analysis uses univariate analysis. The population in this study was 56 people and the sample was 36 people with a sampling technique, namely simple random sampling Result: The research results showed that democratic parenting was 23 respondents (63.9%), permissive parenting was 9 respondents (25.0%) and authoritarian parenting was 4 respondents (11.1%). Conclusion: Most respondents apply a democratic parenting style to preschool-aged children at Al-Khairaat Kindergarten, Loji Village, Parigi Moutong Regency. The advice from this research is that it is hoped that parents and schools will pay attention to which parenting style will be given to children so that they can develop optimal emotional development.